An investigation of how Kampala teenagers who read Straight talk negotiate HIV/AIDS messages - Kaija, Barbara Night Mbabazi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
This study is a qualitative ethnographic investigation of how teenagers in Kampala, Uganda, who read the HIV/AIDS publication aimed at adolescents, Straight Talk, negotiate HIV/AIDS messages. It seeks to establish to what extent these secondary school teenagers accept the key messages (known as ABC; Abstain, Be faithful or use a Condom) and understand the factual aspects of the messages about HIV/AIDS, its process of transmission and prevention. It also seeks to probe how the lived realities of the teenagers affect their particular negotiations of the HIV/AIDS messages. It includes a focus on how proximity to HIV/AIDS, gender and family economic disposition might affect teenagers, negotiation of the HIV/AIDS meanings. To investigate the respondents' reception of HIV/AIDS messages, the study employed focus groups that consisted of two stages, namely the 'news game' and group discussions. In the 'news game' stage (Philo, 1990; Kitzinger, 1993) the teenage participants were required to produce a version of a one-page copy of an HIV/AIDS newspaper targeting teenagers. In the second stage of the focus group a structured discussion probed the teenagers' negotiation of the HIV/AIDS media messages. In the news game, the teenagers on the whole reproduced the key Straight Talk HIV/AIDS messages 'Abstain, Be faithful or use a Condom' and also images showing the effects of HIV/AIDS but featured fewer images depicting the factual aspects of HIV/AIDS process of transmission and risky behaviour. In the structured discussion that followed the news game, it was evident that not all the teenagers necessarily believed the messages they produced. In spite of producing the ABC Straight Talk messages, some of them were uncertain and confused about the absolute safety of the condom because of fears that they were either porous, expired or would interfere with sexual pleasure. Secondly, though many of the teenagers in the study reproduced images that showed that they consider marriage as desirable and talked about their desire to abstain from sex till marriage, a considerable number think abstinence is not achievable due to competing values. Thirdly, the participant teenagers could differentiate between HIV and AIDS but many did not realise that with the advent of anti-retroviral drugs even people who have AIDS can look normal. In spite of repeating the Straight Talk message that "no one was safe" and being aware of the risky behaviour that their fellow teenagers get involved in, the teenagers seemed to think that their age cohort is safe from HIV and it is the adults who are likely to infect them. The study findings further indicate that the teenagers' lived experience at times influence their negotiation of HIV/AIDS media messages. This was probed in terms of economic standing, gender and proximity to HIV/AIDS. In relation to gender one surprising discovery was that certain girls in the study feared getting pregnant more than getting HIV/AIDS. The study finally suggests that these findings are of significance for designing future media initiatives in relation to HIV/AIDS.
Keywords: AIDS (Disease) -- Uganda -- Kampala; Straight Talk Foundation; AIDS (Disease) -- Social aspects -- Uganda -- Kampala; AIDS (Disease) in adolescence -- Uganda -- Kampala; Teenagers -- Diseases -- Uganda -- Kampala; AIDS (Disease) -- Study and teaching; AIDS (Disease) in mass media; Teenagers -- Sexual behavior -- Uganda -- Kampala; AIDS (Disease) -- Prevention -- Uganda -- Kampala